Doxorubicin Induced Hepatotoxicity, Apoptosis and Renal Dysfunction: Role of Hesperidin in Potentiation or Attenuation in Male Wistar Rats - Akwari, Ada; George, Esther; Obia, Ukwula; Nyirenda, Moses; Mbuki, Reuben; Nkanu, Etah E. (British Journal of Healthcare and Medical Research, 2025)
The common side effect of doxorubicin use in the treatment of neoplasms is cardio-hepatotoxicity and nephrotoxicity among others. Other treatment measures has been sort to alleviate the outrageous suffering of cancer patients. Hesperidin, a natural plant product from citrus plants has an antioxidant and protective property. The aim of the study was to find out the effect of hesperidin and captopril on doxorubicin induced liver and kidney injury as well as apoptotic activity. In this study, twenty five male Wistar rats weighing 160-180g were randomly selected into five groups (G1-G5)containing five rats each. G1 (control), received normal feed, G2 received 5mg/kg body weight of Doxorubicin(doxo) orally. G3 received 50mg/kg of hesperidin, G4 received 5mg/kg body weight of Doxorubicin(doxo)plus Hesp. While G5 received 5mg/kg body weight of Doxorubicin(doxo)plus Captopril(oral). Treatment lasted for 28 days. Blood samples were collected via cardiac puncture and centrifuged at 1000rpm for 10minutes. Results obtained showed elevated levels of malondialdehyde, Urea, creatinine and total proteins. Liver enzymes (AST, ALT, ALP, GGT), Caspase 3, Bax and Bcl2 were significantly (p<0.05) raised. Treatment with hesperidin and captopril respectively, significantly (p<0.05) decreased the parameters in all treatment groups when compared to doxo group. We conclude that hesperidin transiently attenuates apoptosis and ameliorates toxic effects of doxorubicin on the liver and kidney .